Extensions of the first Borel-Cantelli Lemma in Riesz spaces - Mushambi, Nyasha Takunda (My University, 2018)
The classical First and Second Borel-Cantelli theorems as well as the Kolmogorov Zero-One Laws have been extended to the abstract setting of Riesz spaces by Wen-Chi Kuo, Coenraad C. A. Labuschagne and Bruce A. Watson. This dissertation aims to extend upon the work of these authors. In particular, an extension of the Barndorﬀ-Nielsen Zero-One Law to the Riesz space setting.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in fulﬁlment of the requirements for the degree of Master of Science, February 2018
Keywords: Probabilities; Measure theory; Mathematical statistics